Characterisation of South African indigenous microalgae for biofuel production potential - Grobler, Jasper (My University, 2019)
Bio-energy has been widely studied as a renewable energy source. One of the main challenges of traditional bio-energy is that it competes with local food and agriculture industries for feedstock and arable land. Bio-energy derived from a microalgal biomass feedstock has the potential to be used without competing with agriculture and food industries. Bio-diesel and bio-ethanol can be generated from cellular lipids and carbohydrates, respectively, isolated from microalgal biomass. In this study we evaluated the potential of South African indigenous microalgae for use in bio-diesel and bio-ethanol production by firstly identifying an isolate suitable for biofuel production, suitable cultivation medium and analysing bio-fuel properties. Fifteen South African indigenous microalgal isolates from the Microalgal Culture Collection of South Africa (MiCCSA) were cultivated at 2 L scale and characterised to derive their bio-fuel production potential. The isolate referred to as WCB 4.1, identified as Acutodesmus bajacalifornicus, showed good potential for use in bio-energy production, and was used in subsequent studies throughout the work. To explore the potential of increasing lipid, carbohydrate and yield rates of WCB 4.1, eleven potential microalgal cultivation mediums were identified. WCB 4.1 showed the highest growth rate in the JG medium (in-house formulation), with a competitive growth rate of 0.47 d-1. WCB 4.1 showed the highest biomass productivity in the Hase medium, with a relatively low productivity of 53.1 mg/L/d. To be able to fully understand the effect different cultivation mediums have on the cultivation of WCB 4.1, the effect of medium variation on biomass biochemical composition was considered. The bio-diesel yield rate of WCB 4.1 grown in four of the cultivation mediums was superior to that of first-generation bio-energy crops. However, the bio-ethanol yield rate from WCB 4.1 was inferior to first generation bio-energy crops. Utilising bio-diesel property predictive formulas it was possible to predict the properties of bio-diesel generated from WCB 4.1 biomass cultivated in eleven different mediums. It was found that WCB 4.1 biomass from eight of the mediums adhered to South African summer grade bio-diesel standards. WCB 4.1 shows potential to become a commercially competitive strain for bio-energy production, which can produce more bio-diesel per hectare annually than traditional food crops. The bio-energy yield rates of WCB 4.1 do however need some improvement to be able to have bio-energy productivities similar or higher than microalgal bio-energy productivities described by other sources. The key to unlock the potential of WCB 4.1 would be in further process development and improvement.
A dissertation submitted to the Faculty of Engineering and the Built Environment in fulfilment of the requirements for the degree of Master of Science in Engineering, University of the Witwatersrand, Johannesburg, 2019
Keywords: Microalgae; Biotechnology